2020
DOI: 10.1016/j.afos.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in COVID - 19: Dousing the fire or averting the storm? – A perspective from the Asia-Pacific

Abstract: COVID-19, the acute respiratory tract infection (RTI) caused by the Coronavirus, Sars-CoV-2, has swept around the world. No country has been spared from its onslaught. Treatments that can reduce the risk of infection and mortality from the disease are desperately needed. Though high quality randomized controlled trials are lacking, some observational and interventional studies that explore the link between vitamin D and RTIs exist. Vitamin D modulates both innate as well as adaptive immunity and may potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 74 publications
1
33
1
Order By: Relevance
“…This review showed that improving vitamin D status in the general population has a potential benefit in reducing the risk of acquiring COVID-19 infection. Evidence by Chandran et al also recommends supplementation of vitamin D in patients with COVID-19 ( 36 ). A meta-analysis of randomized controlled trials (RCTs) concluded that the use of vitamin D supplements was associated with lower mortality in adults ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that improving vitamin D status in the general population has a potential benefit in reducing the risk of acquiring COVID-19 infection. Evidence by Chandran et al also recommends supplementation of vitamin D in patients with COVID-19 ( 36 ). A meta-analysis of randomized controlled trials (RCTs) concluded that the use of vitamin D supplements was associated with lower mortality in adults ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, and through its anti-inflammatory actions, vitamin D acts as a key factor in the regulation of the adaptive immunity as it can suppress the responses induced by the T helper cell type 1 (Th1) and thus contributes to the attenuation of the cytokine storm particularly that of interleukin 6 (IL6). The latter is considered as the trigger of the systemic extension of inflammatory response, and of numerous acute complications, particularly pulmonary ones, observed in severely affected COVID-19 patients ( 3 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the above mentioned arguments, several studies have been designed with the aim to explore that association. Although the findings are very heterogeneous and inconsistent, most of the observational studies agreed on a strong and significant association between vitamin D deficiency and the risk of both upper and lower respiratory tract infections ( 3 , 9 ). There is even some research demonstrating that adequate vitamin D levels correlate with a better prognosis in a number of respiratory infections such as those caused by Mycobacterium tuberculosis and the common influenza virus ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These comorbidities play a vital role in segregating AI models that can be independently trained for effective diagnosis and COVID-19 severity prediction. The selected comorbidity studies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] were taken from https://pubmed.ncbi.nlm.nih.gov/ . Figure 5 shows the number of subjects with comorbidities enrolled in the ARDS-based studies.…”
Section: Comorbidity and Ardsmentioning
confidence: 99%